Absence of Langerhans cells resulted in over-influx of neutrophils and increased bacterial burden in skin wounds - Wang, Zheng-Cai; Hu, Yan-Yan; Shen, Xiao Z.; Tan, Wei-Qiang (Cell death & disease, 2024)
Langerhans cells (LCs) are resident dendritic cells in the epidermis and their roles in presenting antigens derived from microorganisms present in the skin has been well appreciated. However, it is generally thought that incoming neutrophils are mainly responsible for eradicating invading pathogens in the early stage of wounds and a role of LCs in innate immunity is elusive. In the current study, we showed that wounds absent of LCs had a delayed closure. Mechanistically, LCs were the primary cells in warding off bacteria invasion at the early stage of wound healing. Without LCs, commensal bacteria quickly invaded and propagated in the wounded area. keratinocytes surrounding the wounds responded to the excessive bacteria by elevated production of CXCL5, resulting in an over-influx of neutrophils. The over-presence of activated neutrophils, possibly together with the aggravated invasion of bacteria, was detrimental to epidermal progenitor cell propagation and re-epithelialization. These observations underscore an indispensable role of LCs as effective guardians that preclude both bacteria invasion and damages inflicted by secondary inflammation. Highlights Langerhans cells (LCs) are considered resident dendritic cells in the epidermis and their roles in presenting antigens derived from microorganisms present in the skin has been well appreciated. However, the role of LCs in wound healing is controversial. In this study, we demonstrate that wounds absent of LCs had a delayed closure. Mechanistically, LCs may be the primary cells in warding off bacteria invasion at the early stage of wound healing. Without LCs, propagation of commensal bacteria was evident in the early stage of wounds, which stimulated keratinocytes to overproduce CXCL5, a neutrophil chemokine. Over-influx of 3neutrophils significantly slowed epidermal progenitor cell propagation, re-epithelization and wound healing in the absence of LCs.